2016
DOI: 10.1007/s10086-016-1597-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of wood on humans: a review

Abstract: It is empirically known that wood can cause a comfort enhancement effect in humans. On the other hand, not enough scientific knowledge based on evidence-based research is available on this subject. However, data using physiological indices have increasingly accumulated in recent years. This review provides an overview of the current situation for peer-reviewed reports related to the physiological effects of wood. We reviewed reports that elucidated the effects of wood-derived stimulations on the olfactory, vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 48 publications
2
56
0
Order By: Relevance
“…Previous studies examining stress-related psychophysiological responses to wood in the built environment Many studies have examined the psychophysiological effects of exposing building occupants to wood, as detailed in recent reviews (Burnard & Kutnar, 2015;Ikei, Song, & Miyazaki, 2017;Nyrud & Bringslimark, 2010). Previous studies demonstrated individuals had varied psychophysiological responses to visual exposure to interiors with wood (sometimes compared to other materials) using a variety of indicators.…”
Section: Supporting Recovery From Stress In the Built Environmentmentioning
confidence: 99%
“…Previous studies examining stress-related psychophysiological responses to wood in the built environment Many studies have examined the psychophysiological effects of exposing building occupants to wood, as detailed in recent reviews (Burnard & Kutnar, 2015;Ikei, Song, & Miyazaki, 2017;Nyrud & Bringslimark, 2010). Previous studies demonstrated individuals had varied psychophysiological responses to visual exposure to interiors with wood (sometimes compared to other materials) using a variety of indicators.…”
Section: Supporting Recovery From Stress In the Built Environmentmentioning
confidence: 99%
“…6d, p < 0.01). With regard to "uneven-flat" feeling, hinoki, which was perceived as "slightly to moderately 6 Subjective feeling measured by the modified semantic differential method after touching hinoki or marble materials. a "Comfortable" feeling, b "relaxed" feeling, c "natural" feeling, d "warm-cold" feeling, e "uneven-flat" feeling, f "dry-moist" feeling, g "softhard" feeling.…”
Section: Psychological Effectsmentioning
confidence: 99%
“…Wood is a familiar, natural material that is used in houses and furniture, and it is empirically known to have a relaxing effect on humans [6]. A review outlining the current state of research regarding the physiological effects of wood-derived stimulation on humans [6] reported that data on the physiological effects of olfactory stimulation have continued to accumulate, following the development of physiological measurement technology in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For exposures without ground contact (Class 3 according to EN 350 [1]), it is possible to use hydrophobization in the form of a coating [12]. Hydrophobic coatings have the advantage of easier application and lower cost compared to thermal treatment, acetylation, or plasma treatment, and they also preserve the original appearance of the wood, thereby positively influencing human perception [13].…”
Section: Introductionmentioning
confidence: 99%